Implementasi E-Raport Berbasis Chatbot Studi Kasus di SMA Dipoenogoro 2 Jakarta - Dadang Iskandar Mulyana; Muhammad Arfan Irsyad Rowis; Dedi Iskandar; Ari Surya Jaya (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
With the rapid development of modern information and technology in all fields, including education, the order of learning activities in schools can be changed to become more effective and efficient. A transcript is the result of each student or student's values ​​during a semester entered or recorded in a report. To increase the effectiveness and efficiency of report card distribution, a simple electronic report or electronic report card program has been developed that student parents can use to know their sons and daughters' school performance. The use of electronic reporting is therefore considered very important given that it is currently a condition of recovery for all sectors affected by the Covid-19 pandemic. , integrated with Python, MySQL database and linked to web program, chatbot based and implemented in SMA Dipoenogoro 2 East Jakarta. The way it works is by using an autoresponder program that calls a database of student grades stored in a database. The student's grades are then converted to a PDF file, and the student's parents simply need to download the transcript and the student's study link. Output the results in PDF format and print without coming to school. In the methods used, the collection technology consists of: Literary observations, interviews, research. The application development method is Extreme Programming, and the service implementation method is implementation method (evidence-based practice) and public relations. The socialization and presentation results showed a good and positive response among all parties involved, i.e. the students' parents and teachers. From a student's parent's point of view, the system is very welcome as it allows them to easily know their child's academic performance. Of course, parents can monitor their child's developmental learning patterns during the school year. Teachers, on the other hand, perceive this advantage as being more effective and efficient. From entering academic records for each student to distributing transcripts, supporting learning activities in modern schools where technology is rapidly developing can be very useful.